PROSPECTIVE TRIAL INCORPORATING PRE-/MID-TREATMENT [(18)F]-MISONIDAZOLE POSITRON EMISSION TOMOGRAPHY FOR HEAD-AND-NECK CANCER PATIENTS UNDERGOING CONCURRENT CHEMORADIOTHERAPY - Lee, Nancy (2009)
PURPOSE: To report the results from a prospective study of a series of locoregionally advanced head-and-neck cancer patients treated with platinum-based chemotherapy and intensity-modulated radiotherapy and to discuss the findings of their pre-/mid-treatment [(18)F]-misonidazole ((18)F-FMISO) positron emission tomography (PET) scans. METHODS AND MATERIALS: A total of 28 patients agreed to participate in this study. Of these 28 patients, 20 (90% with an oropharyngeal primary cancer) were able to undergo the requirements of the protocol. Each patient underwent four PET scans: one pretreatment fluorodeoxyglucose PET/computed tomography scan, two pretreatment (18)F-FMISO PET/computed tomography scans, and a third (18)F-FMISO PET (mid-treatment) scan performed 4 weeks after the start of chemoradiotherapy. The (18)F-FMISO PET scans were acquired 2–3 h after tracer administration. Patients were treated with 2–3 cycles of platinum-based chemotherapy concurrent with definitive intensity-modulated radiotherapy. RESULTS: A heterogeneous distribution of (18)F-FMISO was noted in the primary and/or nodal disease in 90% of the patients. Two patients had persistent detectable hypoxia on their third mid-treatment (18)F-FMISO PET scan. One patient experienced regional/distant failure but had no detectable residual hypoxia on the mid-treatment (18)F-FMISO PET scan. CONCLUSION: Excellent locoregional control was observed in this series of head-and-neck cancer patients treated with concurrent platinum-based chemotherapy and intensity-modulated radiotherapy despite evidence of detectable hypoxia on the pretreatment (18)F-FMISO PET/computed tomography scans of 18 of 20 patients. In this prospective study, neither the presence nor the absence of hypoxia, as defined by positive (18)F-FMISO findings on the mid-treatment PET scan, correlated with patient outcome. The results of this study have confirmed similar results reported previously.